A critical exploration of gender analysis : exploring the value and practice of gender analysis through engaging in gender analysis with communities and development staff in Vanuatu : a thesis presented in partial fulfilment of the requirements for the Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Kangisher, Joanna (Massey University, 2007)
This research critically examines development project and programme Gender Analysis (GA) frameworks, trialing them with World Vision Vanuatu (WVV) staff and project communities. A Women’s Equality and Empowerment Framework (WEEF) analysis of the WVV country programme provided a visual overview of the programme, demonstrating that the organisation has a strong concern for women’s issues and were encouraging women’s empowerment. The programme could be improved by engaging in more conscientisation around gender issues. The Harvard Analytical Framework collected rich data on men and women in the communities and helped project staff to get to know the communities better. It also questioned the effectiveness of projects in dealing with gender issues, WVV need to provide equal opportunities for women at the project management level. The Gender Analysis Matrix (GAM) clearly showed project impacts for both men and women. One of the literacy projects had greatly benefited women, but could be improved by running separate classes for the men. The GAM results are not restricted to gender issues; the tool shows potential as a general monitoring framework. Experienced facilitators are needed to get the most out of the frameworks, however anyone can greatly benefit from utilising these tools. No GA framework can replace an awareness of gender issues and the will to work towards a fairer society. GA frameworks that are designed to empower the participants can deliberately or inadvertently be used in an extractive way, while frameworks that are labelled as extractive can be used creatively to empower those who take part. GA sessions provide rich data on gender in a relatively short period of time. While they risk not collecting enough information, the systematic collection and use of some information should help move development work forward.
Keywords: Gender analysis; Vanuatu; Fields of Research::370000 Studies in Human Society